Inflammation and Incretins - Amitabh Hatwal (Indian Journal of Endocrinology and Metabolism, 2012)
Nutrient excess results in systemic inflammation in diabetes contributing to insulin resistance, dyslipidaemia and increased cardiovascular risk. GLP-1 agonists and DPP-4 inhibitors, which are now well accepted therapies for diabetes may play a unique role in modulating this inflammatory process. Incretin based therapies have shown beneficial anti-inflammatory effects on surrogate markers but cardiovascular outcome data is still lacking.